RADIOCARBON INVESTIGATION OF THE SUPERLATIVE AFRICAN BAOBABS FROM SAVÉ VALLEY CONSERVANCY, ZIMBABWE - PATRUT, Adrian; PATRUT, Roxana T.; RAKOSY, Laszlo; LÖWY, Daniel A.; MĂRGINEANU, Dragoș; REDEN, von, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The article reports the radiocarbon investigation results of the superlative African baobabs from Savé Valley, Zimbabwe. Several wood samples collected from these baobab were analysed by AMS (accelerator mass spectrometry) radiocarbon dating. The radiocarbon dates of the oldest samples were 1529 ± 14 BP for Matendere Big baobab, 1179 ± 19 BP for Chishakwe Big tree and 1096 ± 35 BP for Mokore Giant baobab. The corresponding calibrated ages are 1430 ± 15, 1090 ± 40 and 1020 ± 25 calendar yr. The oldest tree from Savé Valley, which we described previously, is the Humani Bedford Old baobab. The radiocarbon date of its oldest sample, 1655 ± 14 BP, corresponds to a calibrated age of 1580 ± 30 calendar yr.